PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. DUA SAMUDERA PERKASA KABUPATEN TANAH BUMBU - Sandi, Ahmad Ari; Karsudjono, Anthonius Junianto (Al-Kalam Jurnal Komunikasi, Manajemen dan Bisnis, 2024)
Ahmad Ari Sandi, Management, 2023, The Influence of Work Motivation and Work Environment on Employee Performance at PT. Dua Samudera Perkasa Tanah Bumbu Regency. This research aims to determine and prove the influence of work motivation and work environment on employee performance at PT. Dua Samudera Perkasa, Tanah Bumbu Regency. The sample in this research was 45 respondents, this research was processed from distributing questionnaires and analyzed using multiple regression analysis SPSS version 26. The research results show that work motivation and work environment simultaneously influence the performance of PT. Dua Samudera Perkasa Tanah Bumbu Regency employees, work motivation and work environment partially influence the performance of PT Dua Samudera Perkasa Tanah Bumbu Regency employees, work environment is the dominant variable that influences the performance of PT Dua Samudera Perkasa, Tanah Bumbu Regency employees.